2009
DOI: 10.1158/0008-5472.can-08-4953
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Embryonic Stem Cell Signature by Histone Deacetylase Inhibitor in NCCIT Cells: Involvement of Nanog Suppression

Abstract: The embryonic stem cell-like gene expression signature has been shown to be associated with poorly differentiated aggressive human tumors and has attracted great attention as a potential target for future cancer therapies. Here, we investigate the potential of the embryonic stem cell signature as molecular target for the therapy and the strategy to suppress the embryonic stem cell signature. The core stemness gene Nanog is abnormally overexpressed in human embryonic carcinoma NCCIT cells showing gene expressio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
55
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 37 publications
0
55
0
1
Order By: Relevance
“…To investigate the roles of distinct epigenetic mechanisms in silencing pluripotency genes, we used embryonic carcinoma cell line NCCIT (19,20), colon cancer cell line HCT116, and cell line DKO1, the hypomethylated derivative of HCT116 that exhibits 95% reduced DNA methylation because of the genetic knockdown of DNA methyltransferases DNMT3B and DNMT1 (21,22). These cell lines were selected because they represent distinct transcriptional contexts of pluripotency genes in the presence and absence of DNA methylation.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the roles of distinct epigenetic mechanisms in silencing pluripotency genes, we used embryonic carcinoma cell line NCCIT (19,20), colon cancer cell line HCT116, and cell line DKO1, the hypomethylated derivative of HCT116 that exhibits 95% reduced DNA methylation because of the genetic knockdown of DNA methyltransferases DNMT3B and DNMT1 (21,22). These cell lines were selected because they represent distinct transcriptional contexts of pluripotency genes in the presence and absence of DNA methylation.…”
Section: Resultsmentioning
confidence: 99%
“…NANOG expression in embryo development is crucial and probably depends on its ability to regulate the expression of OCT4 and SOX2, which have been implicated in transcription regulation of a number of genes in the pluripotency network [20,63]. It was also demonstrated that HDAC1 mediated suppression of OCT4 and SOX2 results in suppression of NANOG [64]. It has been suggested that HDAC1, OCT4 and NANOG form the NODE complex responsible for regulation of gene expression and for maintaining pluripotency [65].…”
Section: Discussionmentioning
confidence: 99%
“…This assay is considered the most stringent in vitro test for determining malignant transformation. 53 It has been shown that the ability of tumor cells to form (10 7 pfu) IV on the indicated day. Lungs were removed on day 12 following tumor challenge, at which time metastases were macroscopically visible (a).…”
Section: Resultsmentioning
confidence: 99%